2017
DOI: 10.3389/fpsyg.2017.00751
|View full text |Cite
|
Sign up to set email alerts
|

Succumbing to the Call of Violence – Sex-Linked Development of Appetitive Aggression in Relation to Familial and Organized Violence

Abstract: Appetitive aggression is the attraction to violent behavior, which can peak in the experience of a combat high. In various war and conflict scenarios, members of armed groups have reported developing a desire to hunt and even kill humans. More recently, we reported that the phenomenon has also been observed in female ex-combatants with varying participation in warfare. Despite recent investigations on risk factors for appetitive aggression, sex-specific pathways in the development of appetitive aggression have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Thus, our results partially replicate previous findings from male cohorts of active soldiers and ex-combatants (MacManus et al, 2013;Nandi et al, 2015). Even though Augsburger et al (2017) could not find any sex differences among former combatants in the context of committed violence, being a male did play a significant role in our regression model for perpetrated violent acts. This may be due to the fact that men are commonly to be found on the frontlines of combat in military groups (Zack-Williams, 2001), which provides more opportunities for violence, whereas women usually engage in parallel to combat also in noncombat tasks such as domestic work, child care, and they are also not deployed to combat during pregnancy (Baines, 2014).…”
Section: Perpetrated Violent Actssupporting
confidence: 88%
See 2 more Smart Citations
“…Thus, our results partially replicate previous findings from male cohorts of active soldiers and ex-combatants (MacManus et al, 2013;Nandi et al, 2015). Even though Augsburger et al (2017) could not find any sex differences among former combatants in the context of committed violence, being a male did play a significant role in our regression model for perpetrated violent acts. This may be due to the fact that men are commonly to be found on the frontlines of combat in military groups (Zack-Williams, 2001), which provides more opportunities for violence, whereas women usually engage in parallel to combat also in noncombat tasks such as domestic work, child care, and they are also not deployed to combat during pregnancy (Baines, 2014).…”
Section: Perpetrated Violent Actssupporting
confidence: 88%
“…Even though studies on sex differences in relation to appetitive aggression have been conducted, findings are not yet conclusive. While some previous investigations indicated lower appetitive aggression among females than males (Weierstall, Schaal, Schalinski, Dusingizemungu, & Elbert, 2011), other studies showed that women can perceive violent acts as equally appealing as men (Augsburger et al, 2017; Meyer‐Parlapanis et al, 2016; Weierstall, Castellanos, Neuner, & Elbert, 2013). Augsburger et al (2017) found a positive correlation between childhood maltreatment, traumatic load, and appetitive aggression in men.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous research indicates that PTSD symptoms are associated with reactive rather than instrumental aggression (Rasche et al, ). Even more important, a study with former members of armed groups points to negative associations between traumatic events and goal‐oriented aggression in women but an opposite pattern for men (Augsburger, Meyer‐Parlapanis, et al, ). And finally, reactive aggression was related to all clusters of PTSD in female war veterans, but only associated with hyperarousal in males, whereas instrumental aggression revealed the opposite picture (Miles et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals exposed to traumatic stress frequently report behavioral regulation difficulties, leading to outbursts of anger and an increased risk for aggressive behavior. These dynamics can perpetuate ongoing cycles of violence (e.g., Augsburger, Meyer‐Parlapanis, et al, ; Hecker, Fetz, Ainamani, & Elbert, ). Evidence for aggression following traumatic stress is provided by a large number of studies that focused on specific groups such as military personnel or war veterans.…”
Section: Introductionmentioning
confidence: 99%